Urgensi Re-Desain Penyelenggaraan Pilkada dengan Satu Pasangan Calon Berdasarkan Dinamika Implementasi di Jawa Tengah dalam Perspektif Pengawasan - Inti Priswari (Jurnal Adhyasta Pemilu, 2021)
This research tries to unravel the patterns that emerge from implementing single-pair candidate elections from electoral supervisors' perspective in Central Java. The aim is to identify the problems of the election, particularly from the electoral supervisory’s point of view. This descriptive qualitative research using the online interview as a primary data collecting method added with a questionnaire and supervisory report as secondary data finds some regulatory gaps regarding the “subject” and “activity” of empty columns. The gap has been the main factor in the issues of the electoral supervisory elections with the single-pair candidate. Moreover, if these gaps are not addressed promptly, it will become an ongoing problem that will re-emerge and even escalate into widespread horizontal conflict. Therefore, it is necessary to redesign the electoral institution of single-pair candidates comprehensively to suppress various potential problems.